Gut Microbiota-Derived Indole-3-Carboxylate Influences Mucosal Integrity and Immunity Through the Activation of the Aryl Hydrocarbon Receptors and Nutrient Transporters in Broiler Chickens Challenged With Eimeria maxima - Park, Inkyung; Nam, Hyoyoun; Goo, Doyun; Wickramasuriya, Samiru S.; Zimmerman, Noah; Smith, Alexandra H.; Rehberger, Thomas G.; Lillehoj, Hyun S. (Frontiers in Immunology, 2022)
Two studies were conducted to evaluate the effects of indole-3-carboxylate (ICOOH) as a postbiotic on maintaining intestinal homeostasis against avian coccidiosis. In the first study, an in vitro culture system was used to investigate the effects of ICOOH on the proinflammatory cytokine response of chicken macrophage cells (CMC), gut integrity of chicken intestinal epithelial cells (IEC), differentiation of quail muscle cells (QMC) and primary chicken embryonic muscle cells (PMC), and anti-parasitic effect against Eimeria maxima. Cells to be tested were seeded in the 24-well plates and treated with ICOOH at concentrations of 0.1, 1.0, and 10.0 µg. After 18 h of incubation, cells were harvested and RT-PCR was performed to measure gene expression of proinflammatory cytokines of CMC, tight junction (TJ) proteins of IEC, and muscle cell growth markers of QMC and PMC. In the second study, in vivo trials were carried out to study the effect of dietary ICOOH on disease parameters in broiler chickens infected with E. maxima. One hundred and twenty male broiler chickens (0-day-old) were allocated into the following four treatment groups: (1) basal diet without infection (CON), (2) basal diet with E. maxima (NC), (3) ICOOH at 10.0 mg/kg feed with E. maxima (HI), and (4) ICOOH at 1.0 mg/kg feed with E. maxima (LO). Body weights (BW) were measured on days 0, 7, 14, 20, and 22. Jejunal samples were collected for lesion score, and the transcriptomic analysis of cytokines and TJ proteins. Data were analyzed using PROC MIXED in SAS. In vitro, ICOOH increased the expression of TJ proteins in IEC and decreased IL-1β and IL-8 transcripts in the LPS-stimulated CMC. In vivo, chickens on HI diet showed reduced jejunal IL-1β, IFN-γ, and IL-10 expression, and increased expression of genes activated by aryl hydrocarbon receptors and nutrient transporters in E. maxima-infected chickens. In conclusion, these results demonstrate the beneficial effects of dietary ICOOH on intestinal immune responses and barrier integrity in broiler chickens challenged with E. maxima. Furthermore, the present finding supports a notion to use microbial metabolites as novel feed additives to enhance resilience in animal agriculture.